Treason Medieval and Early Modern Adultery, Betrayal, and Shame - Tracy, Larissa (Explorations in Medieval Culture, 2019)
Set against the framework of modern political concerns, Treason: Medieval and Early Modern Adultery, Betrayal, and Shame considers the various forms of treachery in a variety of sources, including literature, historical chronicles, and material culture creating a complex portrait of the development of this high crime.; Readership: All interested in the history and literature of medieval and early modern treason, adultery, betrayal, and shame, especially as it pertains to legal arguments and social concerns, such as gender.